Whose voice counts? Gender, power, and epistemologies in the seminary classroom - Wright, Almeda M. (Teaching theology and religion, 2019)
This article wrestles with the question "whose voice counts?" as an entrée into a discussion of the challenges students encounter in learning to value different epistemologies and that professors encounter in attempting to teach for inclusion of voices. The essay reflects on an experience teaching a graduate seminar on gender and epistemology in which students encounter challenges reflecting on readings that present theology in the form of personal narratives, rather than in a more abstract or theoretical form. Course content and genres of writing are both gendered and subject to power dynamics associated with the uneven treatment of different types of knowledge. The paper focuses primarily on the lens of gender but notes as well the intersectional nature of gender - and the ways in which the course dynamics are complicated by the race, sexuality, and even the class of the authors, students, and teacher. The paper makes two substantial arguments. First, it names a pedagogical meta-question at the intersection of gender and pedagogy: Even when women are on the syllabus, how are educators ensuring that the epistemologies at work in their classrooms allow for equal authorial authority in the classroom? Second, the paper challenges educators to make changes in their classrooms to allow students time to engage and employ epistemologies they discuss and to see the importance of these practices for wider systemic change in institutions and society.